ANTIBACTERIAL ACTIVITIES OF MANGROVE PLANT EXTRACT (Rhizophora stylosa) TO THE GROWTH OF BACTERIA Vibrio parahaemolyticus - Agus Triwanda Wanda; Yuni Puji Hastuti; Sinung Rahardjo (Politeknik Kelautan dan Perikanan Dumai, 2023)
Vibrio parahaemolyticus is a gram-negative halophilic bacterium that lives in estuaries and beaches. These bacteria are agents that cause septicemia in shrimp during the larval and post larvae period. This study aims of this experiment is to determine the effect of mangrove leaf, root, stem and fruit extracts of Rhizophora stylosa growth of the V. parahaemolyticus bacteria. The experimental design used a completely randomized design (CRD) with positive control treatment (Papper disk containing chloramphenicol); Negative control (Papper disk containing methanol) P1 = mangrove extract 100 mg/L; P2 = 200 mg/L mangrove extract; P3 = 400 mg/L mangrove extract and in doing it on 3 times. The research parameter was measuring the bacterial inhibition zone. The results showed that the mangrove leaf, root, stem and fruit extracts of R. stylosa significantly affected on the inhibition zone and of high concentrations of the leaf, root, stem extract concentrations of R. stylosa mangrove fruit, the wider the bacterial inhibition zone. The concentration of 400 mg/L extracts of leaves, roots, stems and fruit heads of R. stylosa mangroves was the most effective concentration to inhibit the growth of V. parahaemolyticus bacteria, which showed an average root inhibition zone of 9.5 mm, leaves 7.7 mm, stems 6.5 mm, and fruit heads 4.8 mm.